Sonographic Demonstration of Intracranial Hemorrhage in a Fetus with Hydrops Fetalis due to Rh Alloimmunization after Intrauterine Intravascular Transfusion: A Case Report and Review of the Literature - Rauf Melekoglu; Ebru Celik; Hasim Kural (Hindawi Limited, 2018)
Intrauterine transfusion is the most common and successful intrauterine procedure for the treatment of fetal anemia due to red cell alloimmunization. Fetal intracranial hemorrhage is a very rare complication of intrauterine transfusion in patients with Rh(D) alloimmunization and it has been demonstrated only in a few case reports in the literature. Herein, we described a case of grade IV intraventricular hemorrhage that was diagnosed following the first intrauterine transfusion and reviewed the literature about the fetal intracranial hemorrhage that occurred after intrauterine intravascular transfusion procedure.